Effect of NPK Compound Fertilizer Normal and Nano on Mineral and Protein Content of Three Species of a Piaceae Plants - Dhafir A. Jameel (Journal of Global Pharma Technology, 2018)
An experiment was conducted under the conditions of Al-Diwaniya governorate in a special nursery was specially constructed for the experiment during the autumn season (2016 - 2017) in order to determine the effect of adding the different levels of balanced NPK fertilizer (20-20-20) normal and nano to the soil of three species ‎of A piaceae (cumin, anise and sweet fennel) and their interference in mineral and protein content of seeds. The factorial experiment that consist of two factor and with three replicates was designed by Randomized Complete Blocks Design (RCBD); the first factor consisted of three species of A piaceae plant that above-mentioned, while second factor included seven levels of the NPK compound fertilizer balanced (control, normal NPK at recommended level, nano NPK at recommended level, normal NPK at double recommended level, nano NPK at double recommended level, Mixture NPK (Normal + Nano) at recommended level, Mixture NPK (Normal + Nano) at double recommended level).The means of the treatments was compared with a significant difference in the use of the least significant difference (LSD) at the probability level (p ≤ 0.05). The results showed the superiority of sweet fennel plant in seeds content of total phosphorus and potassium versus the superiority of cumin plant in total seeds content of nitrogen and protein. The significant effect of soil-additive fertilizers from normal and nano compound fertilizer in the increase of the majority of the studied traits and recording the highest mean in the NPK mixture at the double recommended or recommended level. The interference between factors gave the same significant effect to the superiority of the individual factors, as well as the improvement traits of more than double in some of them and the difference of response between plants depending on the type of fertilizer.Keywords: NPK; nano; a piaceae; mineral; protein.